2019
DOI: 10.5005/jp-journals-10071-23137
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Patients Leaving against Medical Advice in a Tertiary Care Teaching Hospital

Abstract: Background Leaving against medical advice (LAMA) is a worldwide healthcare problem, occurring due to various contributing factors, seen more commonly indeveloping countries like ours. Aim To retrospectively study the prevalence of LAMA along with its affectingfactors. Methods We screened the hospital record of a tertiary care teaching hospital forone year, after obtaining approval from the institutional ethicalcommittee. Patient demography, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Leaving against medical advice (AMA) is a substantial healthcare challenge across the world and in the United States (U.S.). 1 About 500,000 U.S. patients leave AMA annually. 2,3 While this proportion represents a small percentage of the patients' load in the U.S., 2,4 decisions to leave AMA affect the individual, the caregivers, and the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaving against medical advice (AMA) is a substantial healthcare challenge across the world and in the United States (U.S.). 1 About 500,000 U.S. patients leave AMA annually. 2,3 While this proportion represents a small percentage of the patients' load in the U.S., 2,4 decisions to leave AMA affect the individual, the caregivers, and the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 While this proportion represents a small percentage of the patients' load in the U.S., 2,4 decisions to leave AMA affect the individual, the caregivers, and the healthcare system. 5 Leaving AMA is associated with stigma, and incomplete medical care, 1,5 resulting in increased likelihood to be admitted in a different equidistant hospital, fragmented care, 6 and increased cost of care. 7 The most common reasons for leaving AMA are financial constraints, socioeconomic status, dissatisfaction with treatment, and poor communication with healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Leaving AMA can lead to multiple complications, including an increased risk of readmission, suboptimal treatment outcomes, and an increased use of health care resources. [1][2][3] It is critical to understand why patients elect to leave a hospital AMA. In a qualitative study, Simon et al 1 found that individuals with SUDs often leave AMA due to uncontrolled withdrawal symptoms and pain, perceived stigma and discrimination, and dissatisfaction with care.…”
mentioning
confidence: 99%